2010
DOI: 10.1590/s1806-83242010000300017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of sealing active proximal caries lesions with an adhesive system: 1-year clinical evaluation

Abstract: The objective of this study was to evaluate the effectiveness of a therapeutic sealant to arrest non-cavitated proximal carious lesion progression. The study population comprised 44 adolescents who had bitewing radiographs taken for caries diagnosis. Non-cavitated lesions extending up to half of dentin thickness were included in the sample. In the experimental group (n = 33), the proximal caries-lesion surfaces were sealed with an adhesive (OptiBond Solo, Kerr) after tooth separation. The control group (n = 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
(32 reference statements)
0
13
1
Order By: Relevance
“…Hence, lesion progression and cavitation by strengthening the remaining enamel structures should be hampered [1,3]; recent clinical studies corroborated this concept with dental adhesives [4][5][6][7] and revealed that the resin infiltrant's capability to stop the progress of early carious lesions ranged from some 70 % with deciduous molars after 1 year [8] and with young permanent teeth after 3 years [9] up to approximately 90 % of the cases after 1 [10,11] and after 3 years [12], respectively. A clear advantage of this therapeutic regimen is that no sealant margins are produced on the tooth surface [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, lesion progression and cavitation by strengthening the remaining enamel structures should be hampered [1,3]; recent clinical studies corroborated this concept with dental adhesives [4][5][6][7] and revealed that the resin infiltrant's capability to stop the progress of early carious lesions ranged from some 70 % with deciduous molars after 1 year [8] and with young permanent teeth after 3 years [9] up to approximately 90 % of the cases after 1 [10,11] and after 3 years [12], respectively. A clear advantage of this therapeutic regimen is that no sealant margins are produced on the tooth surface [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…The systematic review and meta-analysis by Ammari et al [35] was based on ten studies (401 participants, split-mouth design), performed in primary and permanent dentition. From the included studies, seven were concluded studies [13,30,31,[40][41][42][43] and the others were ongoing studies with partial [44,45] or follow-up results [46] of already published studies [14,47]. Four of the studies were selected for a meta-analysis due to their low risk of bias.…”
Section: Micro-invasive Treatment Of Proximal Caries Lesionsmentioning
confidence: 99%
“…11 Unlike occlusal lesions, it is not possible to conclude that sealing or infiltrating proximal lesions is superior to controlling lesions by stabilizing the oral ecosystem with good hygiene, dietary control and appropriate fluoride use. 28 Caries lesions may be treated using resin or glass ionomer (GI) sealants. It is uncertain whether one type of sealant performs better than the other.…”
Section: Sealing and Infiltration; Minimally Invasive Treatment Of Nomentioning
confidence: 99%